Effect of Rumen-Protected Glucose Supplementation on Feedlot Performance, Carcass Characteristics, and Meat Quality of Kamphaeng Saen Steers - Tong, P.; Boonsaen, P.; Thirawong, P.; Khongpradit, A.; Sawanon, S.; Buaphan, S. (Faculty of Animal Science, IPB University, 2024)
This study aimed to determine the effects of dietary rumen-protected glucose (RPG) supplementation on feedlot steer performance, blood metabolite, carcass characteristics, and meat quality. Twelve Kamphaeng Saen steers were used with mean ± standard deviation for age 27.9 ± 6.9 months and initial body weight of 471 ± 3.03 kg. Steers were randomly assigned to either a control diet (CON) or a diet supplemented with 200 g/head/d of RPG by top-dressing at each feeding daily (RPG). Both groups were fed the concentrate diet, consisting of 14% crude protein and using rice straw as a roughage source in a ratio of 75:25. After being fed for 120 d, the steers were slaughtered. The feedlot performance, ruminal fermentation, blood biochemical parameters, carcass characteristics, and meat quality were evaluated. The results showed that there were no significant differences in the dry matter intake, average daily gain, feed conversion ratio, gain feed ratio (G:F), blood metabolite, and carcass characteristics between the CON and RPG groups. The marbling score, fat and protein contents of the longissimus dorsi muscle of the steers fed the RPG diet were significantly (p<0.05) greater than those for the steers fed the CON diet. In addition, the cooking loss and shear force of the steers fed the RPG diet were significantly (p<0.05) lower than those for the steers fed the CON diet. These results indicated that rumen-protected glucose has the potential to improve the meat quality of Kamphaeng Saen steers.